Prevalence of Ecto and Endo Parasitic Infections Among Bapard Cattle Farm and Gopalganj District of Bangladesh - Mustafa, Md Murshed Hasan; Islam, Md Rafiul; Rahman, Md Mukhlesur; Talukder, Md Hasanuzzaman (Research in Agriculture Livestock and Fisheries, 2022)
Surveillance was conducted to investigate the ecto-and endo-parasitic (gastrointestinal) infections of bapard cattle farm from July 2020 to June 2021 at the Laboratories of BAPARD and Department of Parasitology, BAU. In the study area, a total number of 600 fecal samples and 250 ectoparasites were collected and investigated. Fecal samples were examined by direct smear method followed by McMaster counting technique under microscope. The overall prevalence of endoparasitic (gastrointestinal) infections was 67.5% and ectoparasitic infection was 56%. Prevalence of endoparasite was more frequent in rainy season (52.35%) followed by summer (26.91%) and winter season (20.74%) whereas prevalence of ectoparasite was more prevalent in summer (34.00%) followed by rainy (12.00%) and winter (8.00%) season. Among the endoparasitic infections,high prevalence of Paramphistomum spp. (20.00%) was found in rainy season whereas Haemonchus spp. (11.67%) and Toxocara spp. (10.83%) were higher in summer season. In cattle, prevalence of Paramphistomum spp. (24.00%) and Haemonchus spp. (15.00%) was higher in adult cattle whereas prevalence of Toxocara spp. (25.00%) and coccidian parasitic infection (17.5%) was higher in calf than adult animal. The overall prevalence of ectoparasite was 56% and tick infestation was highest prevalent (20.00%) followed by lice (16.00%), mange (12.00%) and maggot infestations (8.00%). High humidity (above 70%) and temperature provoke high endo and ectoparasitic infections among cattle populations indicate reduced farm productivity and profitability in the study area. Therefore, training of the cattle farmers on the knowledge and appropriate implementation and use of anthelmintic will help to reduce the morbidity of ecto and endoparasitic infections among cattle populations. Vol. 9, No. 2, August 2022: 145-152